Determination of Heavy Metals in Henna Leaves and Cosmetic Henna Products Available in Zliten, Libya - Ajaj, Ismail A.; Amhimmid, wafaa; Ismail, Hala; Al-Arabi, Tahani; Al-Oraibi, Khawla (Al-Mukhtar Journal of Sciences, 2022)
Henna is widely used by Libyan women as a cosmetic, which may contain lead (pb), cadmium (Cd) and other toxic heavy metals. The purpose of this study was to determine heavy metal content of seven henna products, imported and locally produced in Zliten, Libya. An analytical method was performed using Atomic Absorption Spectrophotometer (AAS). In terms of heavy metal content determination, the results revealed a significant difference between henna leaves and cosmetic henna samples. The premixed henna sample H2 had the highest heavy metal concentrations with a high level of lead (6.952ppm), exceeding the WHO's maximum limit and the (ASEAN) Guidelines on Limits of Contaminants for Cosmetics Heavy metal maximum limits, Lead (Pb) is 1 ppm. Nickel (Ni) levels in (H4=5.201ppm) and (H6=2.023ppm ) henna samples were found to be above the WHO's limit of 1.68ppm. The results indicated that such cosmetics expose consumers to high levels of Pb and Cu, and hence to potential health risks. Thus, investigating the sources and effects of heavy metals in such cosmetics is strongly advised.